Evaluation of the Medically Complex Living Kidney Donor - Yasar Caliskan; Alaattin Yildiz (Journal of Transplantation)
Due to organ shortage and difficulties for availability of cadaveric donors, living donor transplantation is an important choice for having allograft. Live donor surgery is elective and easier to organize prior to starting dialysis thereby permitting preemptive transplantation as compared to cadaveric transplantation. Because of superior results with living kidney transplantation, efforts including the usage of “Medically complex living donors” are made to increase the availability of organs for donation. The term “Complex living donor” is probably preferred for all suboptimal donors where decision-making is a problem due to lack of sound medical data or consensus guidelines. Donors with advanced age, obesity, asymptomatic microhematuria, proteinuria, hypertension, renal stone disease, history of malignancy and with chronic viral infections consist of this complex living donors. This medical complex living donors requires careful evaluation for future renal risk. In this review we would like to present the major issues in the evaluation process of medically complex living kidney donor.